Novi Put Svile: Evropska Perspektiva 2018
DOI: 10.18485/fb_nps.2018.ch15
|View full text |Cite
|
Sign up to set email alerts
|

Crna Gora na ekonomskom i pomorskom putu svile u XXI vijeku i činioci ugrožavanja bezbjednosti

Abstract: Crna Gora je jedna od država osnivača grupe "Put svile" kao osnove za jačanje ekonomskih i trgovinskih veza među državama potpisnicama shodno istorijskoj povezanosti sa ovim putnim i trgovinskim koridorom. Članstvom u ovoj grupi Crna Gora dobija značajan podsticaj privrednom razvoju i stvaranju potencijala za direktne strane investicije. Na ovaj način Crna Gora promoviše slobodno kretanje ljudi, roba i usluga i podstiče razvoj saobraćajnih koridora. Crna Gora kao država stalnog ekonomskog prosperiteta posebnu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In fact, economic depression and rising unemployment constitute an important factor conducive to the development of organized crime in sense of a conducive ground to destructive and illegal activities, and in particular to the creation of criminal organizations. Specifically, criminological research has found a causal link between economic crises and organized crime, proving that in times of economic crises the number of certain forms of organized crime can almost double (Veljović & Rakočević, 2018). Therefore, the globalization of the world economy opens the possibility for an increase in the number of crimes committed in the global economy directly threatening human security, such as frauds in the world market, export of unsafe products, offering prohibited products and Internet services, money laundering, trafficking in human beings and white slaves, prostitution, industrial espionage, arms trafficking, weapons proliferation, environmental pollution and degradation, disease spreading, etc.…”
Section: Traditional Threats To Individual Security In Globalization 40mentioning
confidence: 99%
“…In fact, economic depression and rising unemployment constitute an important factor conducive to the development of organized crime in sense of a conducive ground to destructive and illegal activities, and in particular to the creation of criminal organizations. Specifically, criminological research has found a causal link between economic crises and organized crime, proving that in times of economic crises the number of certain forms of organized crime can almost double (Veljović & Rakočević, 2018). Therefore, the globalization of the world economy opens the possibility for an increase in the number of crimes committed in the global economy directly threatening human security, such as frauds in the world market, export of unsafe products, offering prohibited products and Internet services, money laundering, trafficking in human beings and white slaves, prostitution, industrial espionage, arms trafficking, weapons proliferation, environmental pollution and degradation, disease spreading, etc.…”
Section: Traditional Threats To Individual Security In Globalization 40mentioning
confidence: 99%